Systems and methods of summarizing documents for archival, retrival and analysis - ACQUAVIVA PAUL KEVIN (2013)
Systems and methods of summarizing documents for archival, retrieval, and analysis can be used to provide a convenient summary of the content of scanned document(s). After scanning a document or set of documents, character recognition software identifies the text on the pages. Software can produce a summary of the subjects/themes/keywords in the document(s). This summary can take several forms; e.g. an index of subjects/themes/keywords which can then be printed out as a cover sheet for that stack of documents. Alternately, the summary can be in the form of a topic cloud or histogram. The topic cloud can be made dynamic to allow a user to progressively scroll through pages of documents and watch the topic cloud evolve. The histogram can be made searchable to allow the user to view content of selected pages easily and conveniently.